Evaluation of the level of instructional performance of the Islamic education teachers in the middle schools in the light of the strategies of teaching the understanding of the Quranic text and its interpretation - Masmali, Ali Essa (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to evaluate the level of teaching performance of the Islamic education teachers in the middle schools, in the light of the strategies of teaching and understanding Quranic text and its interpretation. Descriptive and observation inventory methods were used to evaluate the teaching performance of Islamic education teachers in light of the strategies of teaching and understanding Quranic text and its interpretation. The study sample consisted of 30 teachers who were selected in a cluster sampling way. The study resulted in a list of teaching performance in the light of the strategies of teaching and understanding Quranic text and its interpretation. The level of performance on the skills of the strategies before the understanding of the Quranic text and its interpretation was average. The stage of typical reading and the general understanding of the Quranic text was medium. The stage of explanatory discussion and the development of Quranic meanings was weak. The stage of summarizing and linking was medium. Finally, the stage of evaluating the understanding of Quranic and self-learning activities was weak. Overall, the level of teaching performance was moderate. The study found statistically significant differences in strategies before the understanding of the Quranic text and its interpretation and the total score in the direction of the most teaching experience. In the light of the study results. In light of the above, the study recommended that the administration of training Department in education should train the teachers of Islamic education on strategies for understanding and interpreting the Quranic text, especially those that appeared in a weak degree, such as: guiding students to consider the title of Quranic verses, predicting the meanings that can be addressed, and providing an opportunity for students.
Keywords: Evaluation; Teaching performance; Islamic Education teachers; Understanding and interpreting the Quranic text; Strategies of teaching the understanding and interpreting of the Quranic text